EVALUATION OF ORAL HEALTH BEHAVIOR IN DENTIST STUDENTS - Adina Oana Armencia; Magda Ecaterina Antohe; Cristina Tarniceriu; Irina Zetu; Anca Mihaela Rapis; Carina Balcos (Romanian Society of Oral Rehabilitation, 2022)
The accumulation of knowledge and attitudes related to oral health, mainly the prevention, control and treatment of dental diseases, is very important during the training of future dentists. Material and methode: The study group is represented by 180 subjects from the Faculty of Dentistry and the College of Dental Technology. In order to make a correlation between the state of oral health, the level of knowledge in the medical field and the way of application in practice, we used questionnaire used by Al-Omiri and collaborators and an adapted version of the Hiroshima questionnaire. Results and discussion: The results obtained showed that most of the students participating in the study care about their oral health. The HU-DBI score was an average of 3,924 for students in the Faculty of Dentistry and 2,293 for students in the College. Conclussion: The level of academic training influences the oral health behaviour.